Analisis Kepraktisan Pengembangan Media Ajar IPS Berbasis Video Interaktif - Irma Sofiasyari; Isna Amanaturrakhmah; Aan Yuliyanto (Jurnal Elementaria Edukasia, 2023)
Teachers must apply innovative and interactive learning media, which are important to encourage the students' participation. However, based on the preliminary observation, most teachers only applied teacher-centered learning while teaching social studies with textbooks. This research is a part of an R&D that examines the product's practicality. The researchers tested the product within a small-scale group. The researchers took the data from 15 students in the fourth grade at Public Primary School Majalengka A and two teachers. The results showed a percentage of 88% of teachers and a percentage of 87.06% of students found the media practical. The practicality showed that the applied media, the cultural map media based on interaction, was practical for the students of the fourth grade to learn social study